LASER-ABLATION ICP-MS ANALYSIS OF SILICATE AND SULFIDE MELT INCLUSIONS IN AN ANDESITIC COMPLEX II: EVIDENCE FOR MAGMA MIXING AND MAGMA CHAMBER EVOLUTION - Halter W.E.; Heinrich Ch.A.; Pettke T. (My University, 2004)
Laser-ablation microanalysis of a large suite of silicate and sulfide melt inclusions from the deeply eroded, Cu-Au-mineralizing Farallon Negro Volcanic Complex (NW Argentina) shows that most phenocrysts in a given rock sample were not formed in equilibrium with each other. Phenocrysts in the andesitic volcano were brought together in dominantly andesitic-dacitic extrusive and intrusive rocks by intense magma mixing. This hybridization process is not apparent from macroscopic mingling textures, but is clearly recorded by systematically contrasting melt inclusions in different minerals from a given sample. Amphibole (and rare pyroxene) phenocrysts consistently contain inclusions of a mafic melt from which they crystallized before and during magma mixing. Most plagioclase and quartz phenocrysts contain melt inclusions of more felsic composition than the host rock. The endmember components of this mixing process are a rhyodacite magma with a likely crustal component, and a very mafic mantle-derived magma similar in composition to lamprophyre dykes emplaced early in the evolution of the complex. The resulting magmas are dominantly andesitic, in sharp contrast to the prominently bimodal distribution of mafic and felsic melts recorded by the inclusions. These results severely limit the use of mineral assemblages to derive information on the conditions of magma formation. Observed mineral associations are primarily the result of the mixing of partially crystallized magmas. The most mafic melt is trapped only in amphibole, suggesting pressures exceeding 350 MPa, temperatures of around 1,000 °C and water contents in excess on 6 wt%. Upon mixing, amphibole crystallized with plagioclase from andesitic magma in the source region of porphyry intrusions at 250 MPa, 950 °C and water contents of 5.5 wt%. During ascent of the extrusive magmas, pyroxene and plagioclase crystallized together, as a result of magma degassing at low pressures (150 MPa). Protracted extrusive activity built a large stratovolcano over the total lifetime of the magmatic complex (>3 m.y.). The mixing process probably triggered eruptions as a result of volatile exsolution.